A review of modified Organic Rankine cycles (ORCs) for internal combustion engine waste heat recovery (ICE-WHR). (September 2018) - Shi, Lingfeng; Shu, Gequn; Tian, Hua; Deng, Shuai
Abstract: Organic Rankine cycle (ORC) is considered as a rational solution to convert thermal energy of low and moderate temperature heat sources into mechanical work, which currently attracts more and more attention as an effective way for internal combustion engine waste heat recovery (ICE-WHR). Traditional design methods for low-temperature ORCs do not adapt to ICE-WHR suitably due to the specific large-gradient temperature drop characteristics of engine waste heats, and corresponding low-temperature organic fluids meeting with thermal matching and thermal decomposition issues for high-temperature exhaust gas recovery. Hence, there have been a great amount of studies focusing on modified ORCs to achieve a better performance from the aspects of cycle and fluid during the past decade, mainly in 2010s. In this paper, relevant researches of these modified ORCs were reviewed and divided into four parts to approach the ideal cycle, which was defined as the best matching cycle to engine waste heats. From paths of fluid and cycle, high-temperature ORCs (HT-ORCs), mixture ORCs (M-ORCs), ORCs combining with extra loops and dual loop ORCs (DORCs) were summarized. The method of temperature-entropy (t-s) map was applied to provide the approaching degree from modified ORCs to the ideal cycle. The study provides valuable information for stakeholders interested in ORC technologies and gives policymakers perspectives regarding different ORC options for ICE-WHR.